Bimanual Motion Primitives for Manipulating 3D Deformable Objects Having Biological Tissues on a Planar Surface With Passive End-Effectors - Hoang Pham; Pablo Malvido Fresnillo; Saigopal Vasudevan; Wael M. Mohammed; Jose L. Martinez Lastra (IEEE Access)
Manipulating deformable objects (DOs) that change shape during operations poses a challenge for robots due to the complexity of modelling and predicting the object’s state. This challenge is critical for the food industry, where collaborative robots will assist workers in processing and packaging food products. Most meat products are three-dimensional DOs (3D-DOs) composed of biological tissues, which give them viscoelastic and anisotropic properties that make their behaviour highly unpredictable and challenging to model. To address this challenge and minimise food cross-contamination, dual-arm robots and non-actuated end-effectors, such as chopsticks, are used to provide more flexibility, especially when working with objects in confined spaces, and reduce tool actuation time. Our goal is to develop a methodology for manipulating predominant convex 3D-DOs composed of biological tissues on a planar surface, altering their position and orientation while minimising their deformations. To accomplish this, we propose bimanual motion primitives utilising a novel geometric approach. Effectiveness is measured by the Intersection-over-Union ratio and object centroid error metrics through 180 chicken-breast, 36 pork-loin-steak experiments, and 96 comparative experiments with heuristic methods for rigid objects.